Temperature Control System Using Carbon Fiber Filament Based on PID Control for Rabbit Hutches - Wincoko (JST (Jurnal Sains dan Teknologi), 2025)
Rabbits are highly sensitive to temperature fluctuations, particularly during the neonatal phase when thermoregulatory mechanisms are not yet fully developed. Unstable environmental temperatures can induce thermal stress, reduce feed intake, inhibit growth, and increase mortality rates. This study aims to design and evaluate a temperature control system based on a Proportional–Integral–Derivative (PID) controller integrated with a carbon fiber filament heating element for rabbit kits housing, and to compare its performance with a conventional heating system. An experimental–applied approach was employed using a Completely Randomized Design (CRD), involving two treatments: carbon fiber heating with PID control and conventional heating with an on–off thermostat. Data collected included real-time cage temperature, energy consumption (kWh), rabbit welfare indicators (feed intake, respiration rate, and mortality), as well as qualitative data obtained through observation and farmer interviews. Quantitative analysis was conducted using descriptive statistics, ANOVA, Root Mean Square Error (RMSE), and Integral of Absolute Error (IAE), while qualitative data were analyzed thematically. The results demonstrate that the PID–carbon fiber system maintained temperature stability with an average deviation of 0.12 °C, significantly outperforming the control system (1.45 °C). Energy consumption was reduced by 23%, feed intake increased by 21%, respiration rate decreased by 16%, and mortality was lower under the PID-based system. The discussion highlights that the integration of carbon fiber filament heating with PID control enhances energy efficiency, ensures homogeneous heat distribution, and improves overall rabbit welfare. In conclusion, this system shows strong potential to reduce operational costs by up to 30% while increasing productivity, although challenges related to humidity effects on filament durability warrant further investigation.